Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the distance between the points [tex]\((4, 6)\)[/tex] and [tex]\((7, -3)\)[/tex], we'll use the distance formula, which is derived from the Pythagorean theorem. The distance formula is:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Let's assign [tex]\((x_1, y_1) = (4, 6)\)[/tex] and [tex]\((x_2, y_2) = (7, -3)\)[/tex].
Now, substitute the coordinates into the formula:
1. Calculate [tex]\(x_2 - x_1\)[/tex]:
[tex]\[ x_2 - x_1 = 7 - 4 = 3 \][/tex]
2. Calculate [tex]\(y_2 - y_1\)[/tex]:
[tex]\[ y_2 - y_1 = -3 - 6 = -9 \][/tex]
3. Substitute [tex]\(3\)[/tex] and [tex]\(-9\)[/tex] into the formula and square them:
[tex]\[ (x_2 - x_1)^2 = 3^2 = 9 \][/tex]
[tex]\[ (y_2 - y_1)^2 = (-9)^2 = 81 \][/tex]
4. Add the squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 9 + 81 = 90 \][/tex]
5. Take the square root of the sum to find the distance:
[tex]\[ \sqrt{90} \][/tex]
This simplifies to approximately:
[tex]\[ \sqrt{90} \approx 9.486832980505138 \][/tex]
Now, let’s evaluate each given option to find the correct one:
A. [tex]\((4-7)^2 + (6-3)^2 = (-3)^2 + 3^2 = 9 + 9 = 18\)[/tex]
B. [tex]\(\sqrt{(4-7)^2 + (6-3)^2} = \sqrt{(-3)^2 + 3^2} = \sqrt{9 + 9} = \sqrt{18}\)[/tex]
C. [tex]\(\sqrt{(4-7)^2 + (6+3)^2} = \sqrt{(-3)^2 + 9^2} = \sqrt{9 + 81} = \sqrt{90}\)[/tex]
D. [tex]\((4-7)^2 + (6+3)^2 = (-3)^2 + 9^2 = 9 + 81 = 90\)[/tex]
From these evaluations, the correct expression that matches our derived distance formula is:
[tex]\[ \sqrt{(4-7)^2 + (6+3)^2} \][/tex]
Therefore, the answer is C.
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Let's assign [tex]\((x_1, y_1) = (4, 6)\)[/tex] and [tex]\((x_2, y_2) = (7, -3)\)[/tex].
Now, substitute the coordinates into the formula:
1. Calculate [tex]\(x_2 - x_1\)[/tex]:
[tex]\[ x_2 - x_1 = 7 - 4 = 3 \][/tex]
2. Calculate [tex]\(y_2 - y_1\)[/tex]:
[tex]\[ y_2 - y_1 = -3 - 6 = -9 \][/tex]
3. Substitute [tex]\(3\)[/tex] and [tex]\(-9\)[/tex] into the formula and square them:
[tex]\[ (x_2 - x_1)^2 = 3^2 = 9 \][/tex]
[tex]\[ (y_2 - y_1)^2 = (-9)^2 = 81 \][/tex]
4. Add the squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 9 + 81 = 90 \][/tex]
5. Take the square root of the sum to find the distance:
[tex]\[ \sqrt{90} \][/tex]
This simplifies to approximately:
[tex]\[ \sqrt{90} \approx 9.486832980505138 \][/tex]
Now, let’s evaluate each given option to find the correct one:
A. [tex]\((4-7)^2 + (6-3)^2 = (-3)^2 + 3^2 = 9 + 9 = 18\)[/tex]
B. [tex]\(\sqrt{(4-7)^2 + (6-3)^2} = \sqrt{(-3)^2 + 3^2} = \sqrt{9 + 9} = \sqrt{18}\)[/tex]
C. [tex]\(\sqrt{(4-7)^2 + (6+3)^2} = \sqrt{(-3)^2 + 9^2} = \sqrt{9 + 81} = \sqrt{90}\)[/tex]
D. [tex]\((4-7)^2 + (6+3)^2 = (-3)^2 + 9^2 = 9 + 81 = 90\)[/tex]
From these evaluations, the correct expression that matches our derived distance formula is:
[tex]\[ \sqrt{(4-7)^2 + (6+3)^2} \][/tex]
Therefore, the answer is C.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.